A novel, Value-Focused-Thinking based, approach for modelling agro-industrial decisions under scarce information - Mario Luis Chew Hernández; Leopoldo Viveros-Rosas; Verónica Velazquez-Romero (Institute of Research and Community Outreach - Petra Christian University, 2020)
Agro-industrial decision-making is hampered by several, variously-natured, uncertainties. As uncertainty reduction is expensive, the decision modelling process for these industries must strive to use all available information. However, said inclusive effort should be accompanied by an effort to keep modelling assumptions transparent. This work shows the development, from a Value-Focused Thinking perspective, of a model to assess alternatives for improving the operation of a cattle fodder producer. Modelling starts by analyzing and structuring the owner’s objectives and proceeds by systematically characterizing, via value judgments or probability distributions, the connections between structured objectives. Constructing the model over a blueprint of connected objectives allows a faithful representation of the understanding of the system behavior while the methodical, one-connection-at-a-time, modelling procedure renders the assumptions used to operationalize each connection visible, facilitating their replacement if more information becomes available. The modelling approach put forward here can support industrial decision making with limited information.